PENERAPAN TEAM GAMES TOURNAMENT (TGT) DENGAN MEDIA QUIZZWHIZZER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV DI SD NEGERI DUKUH 01 SALATIGA - Safira Roesi; Made Rai Suci Shanti NA (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
This research aims to analyze the implementation of Teams Games Tournament (TGT) using QuizWhizzer as a means to improve mathematics learning outcomes for fourth-grade students at SD Negeri Dukuh 01 Salatiga. The research method employed is classroom action research, involving a sample of 29 students. The study was conducted over two cycles. The findings indicate a gradual improvement in mathematics learning outcomes from the pre-cycle to cycle 2. In the pre-cycle, students exhibited passive engagement, with an average score of 49.14 and a mastery percentage of 41.38%. In cycle 1, there was an enhancement in participation and basic understanding; however, analytical skills remained limited, with an average score of 63.79 and a mastery percentage of 62.06%. In cycle 2, success was achieved, with an average score of 73.62 and a mastery percentage of 82.76%, demonstrating the effectiveness of implementing TGT with QuizWhizzer in mathematics instruction for fourth-grade students at SD Negeri Dukuh 01 Salatiga.